A Study of Metaphor in the Grapes of Wrath by John Steinbeck - ABD ELGOUI, Ouahiba; CHAOUCHE, Souheila (جامعة الوادي - University of Eloued, 2023)
The current study endeavors to delve into the use of metaphors in John Steinbeck's literary work, "The Grapes of Wrath" (1939). Specifically, it seeks to analyze the metaphors employed within the novel and uncover the author's underlying motivations for their inclusion. This research adopts a descriptive analytical approach, utilizing stylistics and formalism as tools for examination. The study is divided into two chapters. The first chapter addresses the theoretical framework, exploring the intricate relationship between metaphor and stylistics. It aims to elucidate how metaphor, as a rhetorical device, enhances and transforms language usage. By delving into the various facets of metaphor through stylistic analysis, this chapter aims to shed light on its impact on speech, communication, and the conveyance of meaning. The second chapter focuses on the analysis of "The Grapes of Wrath," demonstrating the abundant presence of metaphors in the novel and their significance in deciphering the author's intentions.
Literature and Civilization
Keywords: Formalism, John Steinbeck, Metaphor, Stylistics, the Grapes of Wrath